IDENTIFICATION OF FISH SPECIES IN RIVER WATERS BENGALON, SANGATTA AND SURROUNDING AREAS IN KUTAI DISTRICT EAST KALIMANTAN PROVINCE - Suyatna, Iwan; Simarangkir, Omega Raya; Raafi, Muhammad; Irwan, Irwan; Winardi, Eko; Dwisata, Asriyanto; Tawang, Firmansyah; Pranoto, Kris; Nirwan, Ki Agus; Palinggi, Yosep (Jurnal Perikanan Unram, 2025)
The waters of the Bengalon River, Sangatta and surrounding areas are affected by community activities as well as coal mining and oil palm plantations. Fish are one of the aquatic biota affected by these activities. The unavailability of river fish species data is a particular concern in evaluating the condition of river waters. The availability of fish species data is considered important for decision-making considerations that will be applied in an area. As a sustainability effort, monitoring, identification and inventory of river fish in the East Kutai Regency area were carried out. This research was conducted in November 2021-May 2022 in Bengalon River, Sangatta and surrounding areas. Fish identification was carried out at the Hydroceanography Laboratory, Faculty of Fisheries and Marine Science, Mulawarman University. Fish data were analyzed descriptively. Based on the research data, rivers in East Kutai district are dominated by the Cyprinidae family. A total of 43 fish species were identified, 10 of which were marine fish species, generally fishes that live around estuaries (brackish water), including species that live in the sea. Keywords: Cyprinidae, East Kutai, Fish, River